Paleoecology of Pantanal lakes via multiproxy analysis. - Rasbold, Giliane Gessica (2020)
Global climate change influences the precipitation patterns, which can have dramatic effects on aquatic and terrestrial ecology. In order to create mitigation strategies is required a deep understanding of the mechanisms and rates of climate change. Lakes and wetlands are sentinels of environmental changes because their sediments and water columns serve as sensitive records of the climate, hydrology, and anthropogenic (human-induced) processes. The Pantanal, located in the Upper Paraguay River, is considered the largest wetland on Earth, and it performs numerous ecosystem services, has an immense biodiversity and is fundamental to global biogeochemical cycles. The environmental changes that occurred on the western border of the Pantanal during the last 19 cal kyr BP were interpreted based on the paleolimnological analysis of sedimentary cores recovered in the Negra and Cáceres lakes. The cores, show variations in the abundance, diversity, and preservation of sponge spicules, phytoliths, and geochemistry of sediments over time. In the Late Pleistocene, the Lakes Negra and Cáceres were strongly influenced by the South American Monsoon System, with intense fluvial activity during a more humid climate. The accumulation of organic carbon in the Pantanal floodplain lakes varied throughout the Late Quaternary. In the Middle Holocene, however, there were drier periods when these lakes were disconnected from the Paraguay River. High levels of organic carbon have been recorded from ~ 7.3-6 cal kyr BP. The records of δ13Corg, δ15Norg and C/N revealed that the organic matter deposited during this phase in the Gaíva, Castelo, Cáceres, and Negra lakes are the source of aquatic macrophytes. It is suggested that the increase in carbon burial in these lakes occurred in a drier climate, in which there was a decrease in the pelagic area. However, the productive coastal areas remained flooded and without the influence of the flood pulses, which were colonized by extensive mats of aquatic macrophytes. The prolonged drier climate resulted in the desiccation and subaerially exposed lake floor, causing sedimentary gaps close to the transition to the Late Holocene. The data suggest that the lakes in the Pantanal floodplain respond in a complex and sometimes indirect way to global climate change. In this sense, the dynamics of the adjacent river system must be considered when interpreting paleohydrology and vegetation patterns. The results of this study allowed new interpretations about the hydroclimatic controls of the lacustrine carbon cycling in the Pantanal wetlands.